PENGARUH DUKUNGAN ORANG TUA DAN LINGKUNGAN SOSIAL TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN EKONOMI (LINTAS MINAT) DI SMA NEGERI 1 KALASAN - Yulia Metty Budiati; FX. Muhadi (Universitas Sanata Dharma, 2022)
This study aimed to determine whether there were: 1) a positive influence of parental supports on students’ achievements in economics (cross-interest) subjects for high school students in Class XI MIPA and 2) a positive influence of the social environments on students’ achievement in economics subjects (cross interests) for high school students in Class XI MIPA. This research was astudy of ex post facto which was conducted in April 2021. The population of this study were students of Class XI MIPA at SMA Negeri 1 Kalasan, totaling 144 people. The research samples that were 108 students were taken by a random sampling technique. The data were collected using questionnaires and documentation. The hypothesis was tested using the Spearman Rank correlation tests. The results showed that: (1) there was no positive influence of parental support on learning achievements in economic subjects (cross interests) for high school students of Class XI MIPA, with the acquisition of sig. (1-tailed) = 0.067 0.05 and the value of r count = 0.145; and (2) there was no positive influence of the social environments on learning achievements in economic subjects (cross interests) for high school students of Class XI MIPA, with the acquisition of sig. (1-tailed) = 0.065 0.05 and the value of r count = 0.146.Keywords: Student Achievement, Parental Support, and Social Environment.